Lowering dietary glycaemic index through nutrition education among Malaysian women with a history of gestational diabetes mellitus - Shyam, Sangeetha; Arshad, Fatimah; Abdul Ghani, Rohana; Abdul Wahab, Norasyikin; Karuthan, Chinna; S., Nik Shanita; Mohd Yusof, Barakatun Nisak; Kamaruddin, Nor Azmi (Nutrition Society of Malaysia, 2013)
Introduction: Gestational diabetes mellitus (GDM) increases risks for type 2 diabetes and cardiovascular diseases. Low glycaemic index (GI) diets improve cardio-metabolic outcomes in insulin-resistant individuals. We examined the feasibility of lowering GI through GI-based-education among Asian post-GDM women.